Effects of binary polymer-humic soil amendments on soil carbon cycle and detoxication ability of heavy metal pollution - Olga Yakimenko; Lev Pozdnyakov; Maxim Kadulin; Dmitriy Gruzdenko; Irina Panova; Alexander Yaroslavov (Chemical and Biological Technologies in Agriculture)
Abstract Background Synthetic hydrophilic polyelectrolytes are considered as perspective tools to optimize soil properties and find increasing applications in agricultural technologies. One possible polyelectrolyte-based soil conditioner that has shown promise for improving soil hydrophysical properties is hydrolyzed polyacrylonitrile (HYPAN), linear polyanion. Combinations of HYPAN with humic substances in binary polymer-humic soil amendment presumably could provide a synergistic impact. In this study we investigated the effects of HYPAN, two different potassium humates (from lignite and lignosulfonate), and binary compositions of HYPAN with humates in the ratios of 1:1 and 1:2, on soil microbiological activity. We applied polymer solutions (0.9% on a dry matter basis) in a lab experiment and examined how they affected soil respiration, microbial biomass, metabolic quotient, and the decomposition rate constant in soil–polymer mixtures. A concurrent set of studies involved spiking soil–polymer mixes with heavy metals (copper, zinc, lead and cadmium). Results In uncontaminated soil–polymer mixtures both humates stimulated the activity of soil microorganisms, expressed in increased basal respiration, microbial biomass, and mitigation of HM toxicity. The effects of binary polymer-humic formulations and HYPAN were comparable to and close in size to those of humates. On the 90th day, humates increased microbial respiration by 54–77% and HYPAN alone by 30%. Binary compositions were more efficient when combined with humate from lignosulphonate. The maximum increase in microbial biomass was obtained with the same humate both in composition and alone (65 and 91 µg C g−1). Under conditions of HM contamination at the end of the incubation, the levels of microbiological parameters in HM spiked soil–polymer mixtures did not statistically differ from the uncontaminated control. Every polymer formulation helped to partially restore microbial activity while reducing the toxic effects of HM. In these circumstances, humate from lignite both by itself and in combination with HYPAN performed better. The quality of organic matter in both humates and HYPAN was the primary determinant of the impact of the examined amendments. Conclusions Combination of natural humate and synthetic HYPAN stimulated the activity of soil microorganisms, increased their biomass and mitigated the toxicity of heavy metals present in the soil. This allows the use of binary HYPAN-humate formulations to improve the chemical and biological properties of soil and increase its productivity. Graphical Abstract